2018
DOI: 10.5194/bg-15-2891-2018
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen cycling in Sandusky Bay, Lake Erie: oscillations between strong and weak export and implications for harmful algal blooms

Abstract: Abstract. Recent global water quality crises point to an urgent need for greater understanding of cyanobacterial harmful algal blooms (cHABs) and their drivers. Nearshore areas of Lake Erie such as Sandusky Bay may become seasonally limited by nitrogen (N) and are characterized by distinct cHAB compositions (i.e., Planktothrix over Microcystis). This study investigated phytoplankton N uptake pathways, determined drivers of N depletion, and characterized the N budget in Sandusky Bay. Nitrate (NO − 3 ) and ammon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 105 publications
(126 reference statements)
2
28
0
Order By: Relevance
“…Denitrification and anammox remove fixed N by reducing NO 3 − or nitrite (NO 2 − ) and producing nitrogen gas (N 2 ), while DNRA alters the mobility of the fixed N, without removing it, by reducing NO 3 − to NH 4 + . Nitrification and denitrification have been widely studied in rivers and streams as important mediators of N transport (Böhlke et al, 2009;Duff et al, 2008;Groffman et al, 2005;Hinkle et al, 2001;Mulholland et al, 2009;Peterson et al, 2001), and all of these processes have been found in groundwater and lake sediments (Hampel et al, 2018;Li et al, 2017;Miller & Smith, 2009;Rissanen et al, 2013;Rysgaard et al, 1993;Salk et al, 2018;Smith et al, 2015;Smith & Duff, 1988;Smith et al, 1991b;Stoliker et al, 2016;Washbourne et al, 2011). Abiotic reactions, such as the oxidation of iron (Fe +2 ) by NO 2 − producing nitrous oxide (N 2 O), can also contribute to N-species cycling (Klueglein et al, 2014;Klueglein & Kappler, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Denitrification and anammox remove fixed N by reducing NO 3 − or nitrite (NO 2 − ) and producing nitrogen gas (N 2 ), while DNRA alters the mobility of the fixed N, without removing it, by reducing NO 3 − to NH 4 + . Nitrification and denitrification have been widely studied in rivers and streams as important mediators of N transport (Böhlke et al, 2009;Duff et al, 2008;Groffman et al, 2005;Hinkle et al, 2001;Mulholland et al, 2009;Peterson et al, 2001), and all of these processes have been found in groundwater and lake sediments (Hampel et al, 2018;Li et al, 2017;Miller & Smith, 2009;Rissanen et al, 2013;Rysgaard et al, 1993;Salk et al, 2018;Smith et al, 2015;Smith & Duff, 1988;Smith et al, 1991b;Stoliker et al, 2016;Washbourne et al, 2011). Abiotic reactions, such as the oxidation of iron (Fe +2 ) by NO 2 − producing nitrous oxide (N 2 O), can also contribute to N-species cycling (Klueglein et al, 2014;Klueglein & Kappler, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This largely agricultural watershed leads to high nitrogen 370 and phosphorus entering Sandusky Bay. Combining these high nutrient loads with the 371 physical aspects leads to very high concentrations of nitrogen and phosphorus within 372 Sandusky Bay, thus resulting in these cyanobacteria blooms (Planktothrix agardhii) 373 [Davis et al, 2015;Salk et al, 2018] …”
Section: Humans 361 362mentioning
confidence: 99%
“…Since the mid-1990s, harmful algal blooms (HABs) have become the new norm for summer months in the Lake Erie ecosystem [29]. Harmful algal blooms occur in the system when cyanobacteria are provided the right temperature, light, and nutrient conditions to proliferate [28]. When these blooms transpire, they have many adverse impacts.…”
Section: Introductionmentioning
confidence: 99%
“…"Whereas the colonial cyanobacterium Microcystis dominates the cHAB community in offshore regions of western Lake Erie, filamentous Planktothrix has been shown to persist in N-limited bays and tributaries" [28], such as in Sandusky Bay [27,28,32]. Situated on Lake Erie's southwestern coast, Sandusky Bay borders Ohio's Ottawa, Erie, and Sandusky counties ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation